Strengthening the Health Claims of the Poor: Promoting Social Inclusion and Redistribution in the Health Sector - Michael Rowson and Medact. London (MEDICINE, CONFLICT AND SURVIVAL, VOL. 21, NO. 2, 152 - 166 (2005), 2005)
The problems for poor people generated by `disorganised health care markets' in the developing world have grave consequences for their health. In many countries, processes of liberalisation and commercialisation have generated a number of dilemmas for policy-makers, non-governmental organisations and individuals seeking health care. Complex markets for health care provision and financing exist, regulation is lacking and rates of exclusion are high due to the effects of prices and a lack of concerted efforts to make health systems more accessible to the poor. Analysis of health systems and the problems they create for the poor should lead to responses that protect and enhance the rights of poor people to health.